Understanding the Relationship between Mental Workload and Stress in Special Education Teachers - Aquino, Afnani; Senjaya, Sukma; Kurniawan, Kurniawan (GLOBAL HEALTH SCIENCE GROUP, 2024)
Children with Special Needs (CSN) have the right to receive inclusive education with teachers as an important factor and the center of the entire education structure. The results of data collection through Focused Group Discussion with Special Education Teachers (SET) in Pangandaran Regency on 27th October 2022, showed that SET sometimes feel anxious about the behaviors shown by CSN at school, such as eating and drinking indiscriminately from items around them that can threaten children's health. And also feel burdened by the hopes of parents who want their child to recover completely after attending special school. Objective: The purpose of this study is to identify the relationship between mental workload and the level of stress of SLTs in Pangandaran Regency. Method: The method in this study is descriptive correlational with a cross-sectional approach. Primary data were collected using the NASA-TLX questionnaire and the SET Stress Level Questionnaire. There were 82 teachers as respondents using a total sampling technique. Result: Data was collected online through a questionnaire distributed to all special education teachers in Pangandaran Regency. The data was processed statistically using the Spearman Rank test which showed a significance of 0.011 (P value <0.05) with a correlation coefficient value of 0.280 which indicated that the strength of the correlation was sufficient (moderate) with a positive correlation direction. Conclusion: It can be concluded that there is a significant relationship between mental workload and the stress level of special school teachers in Pangandaran Regency.